Sound analysis? Investing podcasts and investor information processing - Coleman, Braiden; Fronk, Karson; Hall, Matthew; Twedt, Brady (Review of Accounting Studies, 2026)
Abstract Despite the rapid growth of podcasts as a source of investment information, we know little about their potential capital market effects. We find that the release of podcasts that provide listeners with firm-specific investment analysis is associated with significant increases in trading activity, particularly among retail investors. When released following earnings announcements, investing podcasts appear to provide information to less-informed investors that helps them better process the news, as podcast discussion is associated with reductions in information asymmetry. This effect is stronger for podcasts that include guests, have greater narrative distinctiveness across speakers, convey information more rapidly, and focus more on fundamental analysis. Podcast discussion is also associated with faster price formation and heightened earnings response coefficients, with no evidence of return reversals. Overall, our results are consistent with investing podcasts helping investors to better process information and provide novel evidence on how this emerging technology impacts capital markets.